Editorial Introduction to the Special Issue “Biomaterials and Biofabrication” - Jangho Kim; Kyunghoon Kim; Hong Nam Kim (Applied Sciences, 2020)
This Special Issue “Biomaterials and Biofabrication” of applied sciences comprises 10 papers that are the latest advances in basic and application research in the field of biomaterials and biofabrication [...]